Dampak Penamaan Laut Natuna Utara terhadap Hubungan Bilateral Indonesia Tiongkok - Ilmi, Nur; Rosyidin, Mohamad (Journal of International Relations, 2020)
Indonesia is the largest archipelago country in the world and consists of 17,504 islands. In July 2017 through the Coordinating Ministry for Maritime Affairs (Kemenko Maritim), Indonesia launched a new map of the Republic of Indonesia. Changes and improvements have occurred in some parts of the Natuna waters into the North Natuna Sea which is still included in the Indonesian Exclusive Economic Zone (EEZ). This study aims to provide an understanding of the impact of the North Natuna Sea policy on Indonesia-China Bilateral Relations and provide an explanation of how Indonesia's bilateral relations are related to violations and overlapping territories that occur in the North Natuna Sea. This research uses qualitative research methods with descriptive research type. Furthermore, this study uses the concepts of International Relations, Bilateral Relations and Diplomacy. The results of this research in the political field are that Indonesia and China agree to jointly maintain the stability of the LCS dispute area by strengthening each other's military. While in the economic field, both agreed not to include conflicts over regional sovereignty, which might disrupt bilateral relations in both investment and trade.